Establishing the Critical Role of Oriented Aggregation in Molecular Solid State Fluorescence Enhancement. Issue 8 (16th January 2018) - Srujana, P.; Radhakrishnan, T. P.
Abstract: The general occurrence of fluorescence emission quenching in molecular aggregates is circumvented in select classes of molecules. This has largely been attributed to the rigidification of the molecule and its environment, which hinders non‐radiative excited state energy loss through structural relaxation; since such an effect should in principle apply to most aggregates and crystals, there must clearly be other critical factors that make the select molecules exceptional. Discovery of three crystalline structures of a new push–pull molecule in its enantiomorphic and racemic forms, exhibiting not only very high, but distinctly different solid state fluorescence enhancements, has now allowed a systematic investigation of the role of intramolecular and intermolecular excited state energy loss pathways. Crystallographic, spectroscopic and computational investigations provide a detailed appraisal of the assembly patterns in the crystals, and rigorous establishment of an inverse correlation between intermolecular energy transfer and solid state fluorescence. The study provides a clear visualization of the critical role of oriented molecular aggregation in solid state fluorescence efficiency enhancement. Abstract : Orientation‐controlled fluorescence : Three crystalline structures of a new push–pull molecule in its enantiomorphic and racemic forms show not only very large but also distinctly different enhancement of the fluorescence emission over the solution. The critical role of specific relative molecular orientations and hence intermolecular energy transfer in effecting the enhancement is established, demonstrating that intramolecular factors alone are insufficient to understand the phenomenon.